THE DEVELOPMENT OF METHODOLOGY OF BANKS’ FINANCIAL STABILITY ASSESMENT BY TAXONOMETRIC METHOD - S. Yehorycheva; М. Khutorna; M. Rudenko; O. Vovchenko; S. Tesliuk; L. Gariaga (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
Abstract. The article examines the methodology of assessing bank’s financial stability. It is researched scientific evolution of financial stability nature definition, discerning endogenous and exogenous approaches. It is proved that financial stability simultaneously feels effect from endogenous and exogenous factors and it should be taking into consideration while managing financial stability of a bank, as well as assessing its level. It is grounded a set of requirements while constructing methodological approach for assessing bank’s financial stability that are as follows: it is necessary to form a set of indicators that would allow to characterize the bank’s activity in complex; it is important to consider the dynamic nature of financial stability; it is significant to take into account how any indicator effects on the bank’s financial stability. It is proved taxonomy method as an effective technology of processing quantitative indicators of bank’s financial stability. We propose to normalize values of indicators by the Euclidean distance tool in order to figure out their deviation from the determined standard values. It is proposed to use a set of indicators for assessing the bank’s financial stability, that are grouped as follows: 1) the quality of capitalization; 2) the level of liquidity; 3) quality of assets; 4) risk-validity of business activity; 5) currency risk; 6) credit risk; 7) profitability; 8) operational risk; 9) interest rate risk; 10) factors of the macroeconomic environment. In general, it is proposed to use thirty-eight indicators which are presented by point and dynamic ones. Practical approbation of the proposed methodological approach is carried out on the example of systemically important banks of Ukraine.